2018
DOI: 10.2298/sos1802163t
|View full text |Cite
|
Sign up to set email alerts
|

Mirostructure and microhardness of aluminum-copper composite reinforced with multi-walled carbon nanotubes prepared by vacuum sintering and hot isostatic pressing techniques

Abstract: In this study, we report the processing, microstructure, and microhardness of aluminum-copper composites reinforced with multi-walled carbon nanotubes (CNTs). Composite powders were prepared by a high energy ball (HEB) milling process then consolidated by vacuum sintering and hot isostatic pressing (HIP) techniques. The specimens show a uniform dispersion of CNTs in the Al-Cu matrix with CNT content up to 1 wt.% and a cluster formation observed with higher CNT content of 1.5 wt.%. The specimens have a relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…From the selected area diffraction pattern, a series of concentric rings corresponding to the (111), (200), (220), (311), and (222) crystallographic planes of the Al-fcc crystal lattice (Fig. 2c) are observed [7]. Fig.…”
Section: Methodsmentioning
confidence: 99%
“…From the selected area diffraction pattern, a series of concentric rings corresponding to the (111), (200), (220), (311), and (222) crystallographic planes of the Al-fcc crystal lattice (Fig. 2c) are observed [7]. Fig.…”
Section: Methodsmentioning
confidence: 99%
“…However, compared to Al, the melting point of Mg is low, so the diffusion of small Mg atoms in the Al matrix is quite rapid, and significant amounts of Mg migrate primarily towards the grain boundaries. Sintering at 600 °C leads to gaps, and the Cu atoms migrate to these gaps [18][19][20][21]. The proposed alloy system created in this study should be able to exhibit much more active behavior than an ordinary Al-Cu binary alloy system.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many studies on using CNTs for MMCs (i.e. Al, Cu, Mg and Ni) have been published which demonstrated that CNTs could enhance the mechanical, thermal and electrical properties of the composites [6][7][8][9][10][11][12][13][14][15][16][17][18]. Among them, CNT/Cu composite is one of the most important composites due to their high potential applications in the electronics and electrical industries [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%